2009
DOI: 10.2223/jped.1914
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pencil grip posture and different desk designs on handwriting performance in children with hemiplegic cerebral palsy

Abstract: Objective: The aim of this study was to investigate the effect of different ergonomic desk designs and pencil grip patterns on handwriting performance in children with hemiplegic cerebral palsy and healthy children. Methods:Twenty-six children with left hemiplegic cerebral palsy and 32 typically developing children were included. The Minnesota Handwriting Assessment was used to evaluate handwriting abilities. Pencil grip posture was assessed with a 5-point rating system. Specifically designed adjustable desks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
(34 reference statements)
0
4
0
6
Order By: Relevance
“…The data indicated a significant difference in the activity execution time and in the Vertical Velocity Peak when the participants used appropriate furniture to their anthropometric measurements, but there was no significant difference in the performance in relation to the vertical acceleration. The use of a table with a 20º slope has been efficient in the parameters of speed and calligraphy size of children with CP and in speed for healthy children, since this furniture can offer a better visuomotor organization (Kavak & Bumin, 2009). Increased speed in writing or drawing means improvement or automatism of the motor act; however, it does not mean improvement in fluency because the student can automate his/her writing and worsen readability (Gimenez, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The data indicated a significant difference in the activity execution time and in the Vertical Velocity Peak when the participants used appropriate furniture to their anthropometric measurements, but there was no significant difference in the performance in relation to the vertical acceleration. The use of a table with a 20º slope has been efficient in the parameters of speed and calligraphy size of children with CP and in speed for healthy children, since this furniture can offer a better visuomotor organization (Kavak & Bumin, 2009). Increased speed in writing or drawing means improvement or automatism of the motor act; however, it does not mean improvement in fluency because the student can automate his/her writing and worsen readability (Gimenez, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…(Alston, 1986;Halıcı, 2019), yazı biçemi (Bara, 2013), yaş, okul, sınıf, cinsiyet, kullanılan el, kağıdın duruşu, kalem tutuş, vücudun duruşu, yazılan metnin türü, yerleşim yeri, okul öncesi eğitim alma (Arslan ve Bağcı, 2017;Arslan ve Ilgın, 2010;Çevik, 2006;Doğan, 2007;Duran, 2011;Erdoğan, 2012;Höbek ve Taşkaya, 2018;Vlachos ve Bonoti, 2006;Yıldız vd. 2015), sınıf öğretmeni Bayraktar, 2006) sıra tasarımı (Kavak ve Bumin, 2009;Medwell ve Wray, 2007) görsel algı (Memiş ve Harmankaya, 2012) kalemi sıkma gücü (Schneck, 1991;Schneck ve Henderson, 1990;Summers ve Catarro, 2003) ve öğrenme güçlüğü (Blöte ve Hamstra, 1991;Fatemeh vd., 2008;Hamstra ve Blöte, 1993; Overlede vd. 2011) arasındaki ilişki üzerinde durulmuştur.…”
Section: Introductionunclassified
“…One study found that 81.3% of children with cerebral palsy were found to write incorrect, uneven and unrecognizable letters 1 ) . Previous studies 1 , 2 , 3 , 4 , 5 ) of handwriting related factors of children with cerebral palsy have been carried out, but these studies had limitations regarding the identification of comprehensive relevant factors and the selection of efficient priorities. In the last ten years, perspectives on outcome assessments of cerebral palsy have been influenced and shaped by the World Health Organization’s International Classification of Functioning, Disability, and Health (ICF) 6 ) , as a guiding principle.…”
Section: Introductionmentioning
confidence: 99%